Penerapan Kaidah Fikih Tentang Niat “Al-Umūru bi Maqāṣidihā” Dalam Kasus Hukum Tindak Pidana Pembunuhan - armaya azmi (Universitas Islam Negeri Sumatera Utara, 2019)
The discourse about “niat (intention)” is a fairly general study in the literature of Islamic studies, this is due to the urgency of the position of intention in human law. One of the principles of fiqh formulated about intention is